Wear Behavior of Ti-Al2O3 Biocomposites in 9 g/L NaCl Solution - Oliveira, André F. F.; Toptan, Fatih [UNESP] (Springer Nature, 2019)
Ti-based biocomposites reinforced with Al2O3 particles were processed by powder metallurgy. Wear behavior was investigated by reciprocating wear tests in 9 g/L NaCl solution. The effect of Al2O3 volume fraction, normal load, frequency and sliding time was studied using 24 full factorial design method. Statistical analysis showed that normal load and frequency, together with the interaction between the reinforcement volume fraction and normal load, was statistically significant on the wear volume loss. The fragmentation of the reinforcement particles during sliding was considered as the key factor in the wear resistance of Ti-Al2O3 composites.
Keywords: biomaterial; composites; metallic matrix; powder metallurgy; titanium